Real-World Treatment Patterns, Clinical Outcomes, and Costs in Patients with Higher-Risk Myelodysplastic Syndromes Across France, Germany, and the United Kingdom - Drummond M; Finelli C; Kristo F; Kelkar SS; Corman S; Raina R; Ashaye A; Dalal M; Haase D (Journal of Blood Medicine, 2025)
Mark Drummond,1 Carlo Finelli,2 Fjoralba Kristo,3 Sneha S Kelkar,4 Shelby Corman,4 Rutika Raina,4 Ajibade Ashaye,3 Mehul Dalal,3 Detlef Haase5 1Beatson Cancer Centre, NHS Greater Glasgow & Clyde, Glasgow, Scotland; 2IRCCS Azienda Ospedaliero-Universitaria di Bologna, Institute of Hematology “Seràgnoli”, Bologna, Italy; 3Global Evidence and Outcomes, Takeda Development Center Americas, Inc., Cambridge, MA, USA; 4Evidence & Access, OPEN Health, Bethesda, MD, USA; 5University Medical Center Göttingen, Göttingen, GermanyCorrespondence: Fjoralba Kristo, Takeda Development Center Americas, Inc., 40 Landsdowne St, Cambridge, MA, USA, Email Fjoralba.kristo@takeda.comBackground: Higher-risk myelodysplastic syndromes (HR-MDS) are associated with increased progression to acute myeloid leukemia (AML) and poor prognosis.Patients and Methods: This chart review characterizes real-world treatment patterns, outcomes, and costs of HR-MDS in France, Germany, and the United Kingdom (UK). Treating oncologists collected data (01 January 2014– 31 December 2016) for adult patients with HR-MDS (revised International Prognostic Scoring System [IPSS-R] score > 3), who received first-line treatment (1LOT) and had ≥ 1 year follow-up post diagnosis or until death. Demographics, clinical characteristics, treatment patterns, outcomes, and healthcare resource use were collected during 1LOT. Kaplan-Meier methods were used for time-to-event outcomes. Costs, applied to resource use, were calculated through 1LOT.Results: Forty-one physicians provided data for 95 patients (France, n=31; Germany, n=29; UK, n=35). At HR-MDS diagnosis, median patient age was 75 years, 62.1% were men, and 60.0% had very high-risk disease per the IPSS-R. Median follow-up was 34.5 months. In 1LOT, 89.5% of patients received azacitidine (median, 12.0 cycles). At the end of 1LOT, 24.2% of patients had a complete and 30.5% a partial remission. From start of 1LOT, median progression-free survival was 24.3 months. Overall survival (unadjusted) was 32.9 months in all patients and shorter in the 33.7% of patients with versus without AML transformation (17.0 vs 52.9 months). Costs for 1LOT were driven by adjunctive therapy and were higher for patients who were transfusion-dependent versus -independent at the start of therapy and who did versus did not have transformation to AML.Conclusion: These results provide real-world data from France, Germany, and the UK on HR-MDS treatment patterns, clinical outcomes, and costs.Keywords: real-world evidence, HR-MDS, IPSS-R, AML